Sistema de produção em casas de farinha: uma contribuição ao processo de consolidação da indicação geográfica da farinha Uarini - Raylene Rodrigues de Sena (2019)
It is generally assumed that cassava is part of the feeding habits of a large number of Brazilian citizens, mainly in its processed variety as flour. In northern and northeastern Brazil cassava flour is an outstanding food item in daily meals, these two regions being the leading ones in consuming the product; for most local producers it is the dominant income source. The state of Amazonas concentrates numerous communities of small-scale rural and indigenous producers dedicated to the production of artisanal flours in traditional flour houses. The industrialization of cassava flour production, especially in southern and southeastern Brazil, motivated communities in the municipality of Tefé (state of Amazonas) and surrounding areas to work together in order to keep going the traditional artisanal production process of cassava flour, as well as to guarantee competitiveness in the market. To accomplish this, these communities joined efforts toward the implementation of changes and adjustments along the production process within flour houses, aiming to comply with structural and sanitary requirements established by the National Institute of Intellectual Property (INPI) in the way to attain the Geographic Indication (GI) registration. The end point of this path was the recognition of the already widely known Uarini flour being produced in that region – the Uarini flour GI was approved in August 2019. With the purposes of better acknowledging the work of Uarini flour producers and observe the changes implemented along the process of GI acquisition, this dissertation focused on the four municipalities that delimit the GI covering area of Uarini flour: Tefé, Uarini, Alvarães and Maraã (state of Amazonas). The central objective of this study was to qualitatively analyze the Uarini flour GI outcome in order to look for its potential contributions to the emergence of new configurations of productive chains, in such a way to explore the circumstances of Uarini flour traditional production process in face of the novel market conditions created by the acquisition of the GI. Results of the research revealed that the changes ultimately implemented along the acquisition process of Uarini flour GI, besides helping to promote the product can also turn the GI itself into an instrument ready to preserve the culture, history and tradition of both flour houses and producers’ “know-how”, additionally providing better living and working conditions such as less physical stress and decreased smoke inhalation. It is also possible that the GI will bring closer together more effectively the Uarini flour brand and consumers particularly living beyond the borders of the state of Amazonas. This means, above all, fighting occasional inaccurate information about the quality of the renowned Uarini flour so that its name will not be improperly associated with other flour brands. According to this perspective, monitoring the production process will be necessary so as to assure the compliance with GI requirements and, consequently, maintain Uarini flour reputation unharmed. Keeping producers engaged with the whole process in the municipalities involved will be necessary, as well as making available to them technical, administrative and financial support.